CSIG-01. EPIGENETIC REPROGRAMMING DRIVES MALIGNANT PERIPHERAL NERVE SHEATH TUMOR (MPNST) DE-DIFFERENTIATION AND TREATMENT RESISTANCE. (12th November 2021) - Vasudevan, Harish; Lastella, Sydney; Sale, Matthew; Casey-Clyde, Timothy; Demaree, Benjamin; Delley, Cyrille; Lucas, Calixto; Magill, Stephen; Liu, John; Chen, William; Braunstein, Steve; Reddy, Alyssa; et al.
Abstract: Schwann cell derived tumors comprising schwannomas, neurofibromas, and malignant peripheral nerve sheath tumors are the most common malignancies of the peripheral nervous system. While schwannomas and neurofibromas are benign, MPNSTs are malignant, metastasize, and respond poorly to treatment. Neurofibromas and MPNSTs are associated with loss of NF1, a tumor suppressor that inhibits Ras/MEK signaling, and MPNSTs alone are distinguished by loss of the Polycomb Repressive Complex 2 (PRC2), an epigenetic regulator of methylation. To understand the genomic mechanisms of Schwann cell tumorigenesis and treatment resistance, we performed DNA methylation profiling, RNA-sequencing, and whole exome sequencing of primary Schwann cell tumor resection specimens (n=119 total: n=66 schwannoma, n=13 neurofibroma, n=40 MPNSTs). Hierarchical clustering identified three epigenetic Schwann cell tumor groups with transcriptional differences in PRC2 target genes associated with Schwann cell differentiation. Integrating biochemical and genomic approaches in primary human tumor cell lines from NF1 intact peripheral nerve, NF1 mutant neurofibromas, and MPNSTs, we found MPNST and neurofibroma cell lines with CRISPR knockout SUZ12 or EZH1/2 neurofibroma cell lines demonstrated repression of Schwann cell differentiation genes and induction of Ras signaling target genes. Further, MPNST cells deficient in PRC2 and NF1 exhibited increased basal active Ras-GTP levels, and therapeutically, PRC2 deficient MPNST cell lines were more resistant to the MEK inhibitor selumetinib and radiotherapy when compared to NF1-deficient neurofibroma cells. Single cell RNA sequencing analysis suggested distinct mechanisms of selumetinib resistance in PRC2 intact neurofibroma cells compared to PRC2-deficient MPNST cells. Taken together, our data demonstrate the importance of epigenetic dysregulation in malignant Schwann cell transformation and suggest differentiation status underlies a novel mechanism of MEK inhibitor resistance.